The diagnostic performance of classical molecular tests used for detecting human papillomavirus (2012)
Cervical samples were evaluated for human papillomavirus (HPV) presence using the hybrid capture-2 (HC2) assay and the polymerase chain reaction (PCR) with three different primer sets (GP5+/6+, MY09/11 and pU1M/2R). PCR results were compared to HC2 and results of all assays were compared to cytological and colposcopy findings. Post-test probability was assessed in individual assays and test combinations. HPV-DNA prevalence was 36.5% with HC2 and 55.2% with PCR. MY09/11 detected HPV-DNA in 38% of samples, GP5+/6+ in 19.1% and pU1M/2R in 16.4%. pU1M/2R and HC2 had the highest concordance (75.31%, k= 0.39 in the whole population; 74.1%, k= 0.5 in women with abnormal cytology). pU1M/2R had the best diagnostic performance, including optimal post-test probabilities and cervical abnormality detection (individually or in a panel of tests). Women positive for pU1M/2R may be at higher risk of disease progression; the assay performance when combined with a Pap smear in cervical cancer screening programs should be evaluated. © 2012 Elsevier B.V..